Pengaruh Kualitas Dan Harga Produk Terhadap Keputusan Pembelian Produk Kosmetik - Putri Jelita; Friska Apriliana; Vicky F Sanjaya (-, 2021)
This study aims to determine whether product quality and price have a significant impact on purchasing decisions for cosmetic products. This research was conducted by observing and surveying consumers of cosmetic products in the Natar District. The population and samples were taken from cosmetic product consumers in the Natar District. Instrument of data collection using a questionnaire with a sampling technique is purposive sampling. The analysis technique, namely path analysis using SMART PLS, is carried out to show whether product quality and price have an impact on purchasing decisions for cosmetic products. The results showed that product quality had a significant impact on purchasing decisions for cosmetic products.Keywords: Quality, Price, Purchase Decision.